CHARACTERIZED OF SLUM AND SQUATTER IN WATERFRONT (CASE - Risyal Rasyid; Arya Ipaldi; Mila Karmilah (International Conference on Coastal and Delta Areas, 2015)
City has always been attractive for people who want to increase the life. Droves of people come and meet the big cities, one of which is Jakarta as the capital city and central government activities in Indonesia. But the phenomenon is not accompanied by the ability and purchasing power of immigrant communities, which in the end they will cause a lot of urban social problems. One of the problems of urban development is the emergence of an increasingly heavy urbanization resulting imbalance pace of development in the city than in the village. The rapid urbanization is not accompanied by the local government's ability to meet the society needs resulted in the growth of unplanned slum and squatters are often even be on areas that should tiodak (riverbanks, the banks of the rail or on lands illegally). This raises many slums, especially in North Jakarta. One of the locations recorded in the slums of Jakarta BPS is a Pejagalan district. Based on the results of the study note that the slums are located in the Pejagalan District has the characteristics as slums are located on the waterfront Keywords: Characteristic, Waterfront, North of Jakarta